Specifics of development of instability in a beam with a current below bursian limit - Galich, A.N.; Gorban, А.М.; Sarukhanyan, G.E. (Вопросы атомной науки и техники, 2013)
A principal possibility of excitation is specified for Bursian instability in flat drift space at beam current which is lower than limited by space charge at the account of initiation of charge accumulation mechanism in the system excitable by wave of density. Times of development of such instability are much greater than electron transit time through the drift space. Встановлена принципова можливість збудження бурсіанівської нестійкості в плоскому дрейфовому проміжку при струмі електронного пучка меншім граничного, обмеженого просторовим зарядом, за рахунок ініціювання механізму накопичення заряду в системі, яка збуджується хвилею густини. Період розвитку такої нестійкості значно перевищує час перельоту електрона через дрейфовий проміжок. Установлена принципиальная возможность возбуждения бурсиановской неустойчивости в плоском дрейфовом промежутке при токе пучка ниже предельного, ограниченного пространственным зарядом, за счет инициирования механизма накопления заряда в системе, возбуждаемой волной плотности. Времена развития такой неустойчивости значительно превосходят пролетное время электрона через дрейфовый промежуток.